Podstawowe założenia metodologiczne w nauce prawa rolnego - Budzinowski, Roman (Wydawnictwo Naukowe UAM, 2013)
Basic Methodological Assumptions in the Science of Agricultural Law S u m m a r y The aim of the deliberations presented in this paper is an attempt to identify the basic methodological assumptions that are, or at last should be, taken into account in the agricultural lawyers’ work. These assumptions are determined by the objectives and conditions of the research and, with regards to the latter, by the characteristics of the analysed legal regulations and the social relationships constituting the object of these regulations. The deliberations are based on two theses that constitute at the same time preliminary assumptions for further discussion: that the study of agricultural law, due to the current and future development of legislation, is void of the temporariness feature, and that a separate, specialised study on the subject is useful and desired. The following methodological assumptions are discussed: (i) the importance of including the agricultural aspect in legal regulations, (ii) the need to maintain the identity of agricultural law, (iii) the requirement of uniformity of regulations on agriculture, (iv) the need to use in the studies on agricultural law the solutions developed in other legal and non-legal sciences. The first three assumptions serve to determine the area of research in agricultural law, while the fourth identifies the manner in which the research should be conducted.

I presupposti metodologici di base nella scienza del diritto agrario R i a s s u n t o Lo scopo delle considerazioni è un tentativo di stabilire i presupposti metodologici di base che sono, o almeno dovrebbero essere, presi in considerazione nei contributi degli agraristi. Questi presupposti vengono determinati dagli obiettivi e condizioni di ricerca, e nell’ambito delle seconde – dalle caratteristiche delle regolazioni giuridiche analizzate e dai rapporti sociali costituenti il loro oggetto. Alla base delle presenti considerazioni si trovano due presupposti che fungono da ipotesi di partenza: lo studio del diritto agrario visto lo sviluppo attuale e futuro della legislazione è privo di caratteristica della temporaneità e le ricerche separate (specialistiche) sono necessarie e utili. L’autore discute i seguenti presupposti metodologici: (A) la necessità di prendere in considerazione l’aspetto agricolo delle regolazioni giuridiche, (B) la necessità di preservare l’identità del diritto agrario e (C) l’unità delle regolazioni agrogiuridiche, (D) la necessità di utilizzare nello studio del diritto agrario il patrimonio di altre scienze giuridiche ed extragiuridiche. I primi tre presupposti devono servire soprattutto a precisare l’area di ricerca della scienza del diritto agrario (in realtà essi sono l’espressione della concezione di separazione del diritto agrario nella struttura dell’ordine giuridico), l’ultimo invece determina il modo in cui la scienza va affrontata.